Barkhausen noise assessment of the surface conditions due to deep hole drilling and their influence on the fatigue behaviour of AISI 4140 - Baak, Nikolas; Schaldach, Fabian; Nickel, Jan; Biermann, Dirk; Walther, Frank (Technische Universität Dortmund, 2018)
In many technical fields, high-strength steels like AISI 4140 are commonly used for highly dynamically loaded parts. Increasing demands on weight, performance and efficiency of the automotive industry lead to increasing demands on material properties. For surface conditioning, optimised machining processes are capable of improving the fatigue performance without increasing the production cost significantly. This paper compares the influence of three different sulphur contents and three different feed rates on the fatigue behaviour of deep hole drilled AISI 4140 fatigue specimens. The specimens were characterised regarding their surface condition, hardness and microstructure, and afterwards they were tested under fatigue loading for performance assessment. These tests were accompanied with Barkhausen noise analysis. The Barkhausen noise signal was detected by a custom-built sensor that is capable of detecting the magnetic values on the bore wall. Using this technique, a load-independent estimation of fatigue damage was established.
Keywords: structural health monitoring; fatigue behaviour; quenched and tempered steel; AISI 4140; 42CrMo4 + QT; surface condition; magnetic Barkhausen noise; 660; Materialermüdung; Gehärteter Stahl; Vergütungsstahl; Barkhausenrauschen